1999
DOI: 10.1046/j.1365-2125.1999.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of drug interaction between omeprazole, lansoprazole, pantoprazole and theophylline

Abstract: Aims Theophylline is a model substrate of cytochrome P4501A2. The ability of the proton pump inhibitors (PPI) omeprazole, lansoprazole and pantoprazole to induce cytochrome P4501A2 has not yet been unequivocally resolved. The aim of this comprehensive study was to compare directly the effect of the three PPI on the absorption and disposition of theophylline. Methods Twenty healthy, nonsmoking, male and female volunteers (extensive metabolisers of cytochrome P4502C19 and Helicobacter pylori negative) participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…In addition, these human hepatocyte cultures have proven also to be a reliable in vitro model for evaluating NCEs as inducers of P450s (Kostrubsky et al, 1999;LeCluyse et al, 2000;Silva and Nicoll-Griffith, 2002). When in vitro P450 induction experiments are conducted at therapeutically relevant concentrations of the NCEs, in most cases, the in vitro data correlate well with clinical observations (Dilger et al, 1999;LeCluyse et al, 2000;Madan et al, 2003).…”
supporting
confidence: 60%
“…In addition, these human hepatocyte cultures have proven also to be a reliable in vitro model for evaluating NCEs as inducers of P450s (Kostrubsky et al, 1999;LeCluyse et al, 2000;Silva and Nicoll-Griffith, 2002). When in vitro P450 induction experiments are conducted at therapeutically relevant concentrations of the NCEs, in most cases, the in vitro data correlate well with clinical observations (Dilger et al, 1999;LeCluyse et al, 2000;Madan et al, 2003).…”
supporting
confidence: 60%
“…Thus, omeprazole and lansoprazole may accelerate pirfenidone metabolism and theoretically decrease its serum concentration and clinical effects; however, in vitro studies are not always consistent with in vivo studies. In vivo interactions of theophylline and caffeine, which are metabolized by CYP1A2, with omeprazole could be clinically negligible in accordance to pharmacokinetic studies [29]. Although the coadministration of pirfenidone and PPIs might not affect the in vivo clinical effects, rabeprazole is better than omeprazole and lansoprazole from the standpoint of CYP1A2 induction.…”
Section: Discussionmentioning
confidence: 64%
“…When hepatocytes are cultured using appropriate conditions which facilitate liver-like cell morphology and expression of liver-specific proteins, CYP enzymes are effectively induced in vitro analogous to the in vivo situation in terms of the magnitude and specificity of induction (37,38). For example, omeprazole is an effective in vitro inducer of human CYP1A2 (37,39), but the EC 50 of omeprazole induction is much larger than the typical exposure in humans treated for gastric ulcers, thus it rarely causes significant clinical drug interactions because the concentration of omeprazole required to induce CYP1A2 exceeds the concentrations achieved in vivo (37,40,41). In addition to CYP enzymes, numerous studies have been reported using primary hepatocyte culture systems to assess induction of a variety of gene targets from Phase II enzymes and transporters (42)(43)(44)(45).…”
Section: Primary Human Hepatocytesmentioning
confidence: 99%